2021
DOI: 10.1186/s12933-021-01219-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of pericardial adipose tissue with left ventricular structure and function: a region‐specific effect?

Abstract: Background The independent role of pericardial adipose tissue (PAT) as an ectopic fat associated with cardiovascular disease (CVD) remains controversial. This study aimed to determine whether PAT is associated with left ventricular (LV) structure and function independent of other markers of general obesity. Methods We studied 2471 participants (50.9 % women) without known CVD from the Korean Genome Epidemiology Study, who underwent 2D-echocardiogra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Moreover, in these mini pigs, the PAT contributes to cardiac fibrosis development [165]. In humans, PAT also contributes to cardiac insulin resistance and left ventricular systolic dysfunction in obese individuals [166,167]. TGF-beta promotes cardiac fibrosis, the formation of cardiac fibroblasts into myofibroblasts.…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…Moreover, in these mini pigs, the PAT contributes to cardiac fibrosis development [165]. In humans, PAT also contributes to cardiac insulin resistance and left ventricular systolic dysfunction in obese individuals [166,167]. TGF-beta promotes cardiac fibrosis, the formation of cardiac fibroblasts into myofibroblasts.…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“… 25 demonstrate consistent findings to our study, reporting positive association of CMR-measured epicardial adiposity and arterial stiffness measured by pulse wave velocity. In an echocardiography study by Kim et al 26 , higher PAT was associated with greater LV mass and poorer LV function by tissue doppler imaging (TDI) velocities. Similar to our study, these associations remained robust after adjustment for classic vascular risk factors, BMI, and waist circumference.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on EAT mainly focused on EAT thickness around the right ventricular free wall or pericardial adipose tissue (epicardial adipose tissue plus paracardial adipose tissue) measured by echocardiogram or CT. Kim et al found that pericardial adipose tissue (PAT) was more strongly associated with the subclinical LV dysfunction than BMI and waist circumference (15). However, EAT is embryologically different from paracardial adipose tissue.…”
Section: Discussionmentioning
confidence: 99%